Toxicity of castrol oil to coffee berry borer [Hypothenemus hampei (Ferrari) (Coleoptera: Curculiondae: Scolytinae)] - Celestino, Flávio Neves; Pratissoli, Dirceu; Machado, Lorena Contarini; Costa, Adilson Vidal; Santos Junior, Hugo José Gonçalves dos; Zinger, Fernando Domingo (Coffee Science - ISSN 1984-3909, 2015)
The oil extracted from the seed of the castor bean has shown to be very promising in the control various pests. The objective of this study was to evaluate the efficiency of the two cultivars of castor beneath two forms of application and in seven concentrations for the control of Hypothenemus hampei (Ferrari). The oil obtained from the castor bean cultivars, IAC 80 and Paraguaçu, in the concentrations of 0.5; 1.0; 1.5; 2.0; 2.5 and 3.0% (v/v) and control (0.0%), in direct and indirect application on the coffee berry borer were used. The cultivars of castor no significant difference in mortality of H. hampei. The direct application of castor oil on the coffee berry borer caused higher mortality than indirect application, except for the concentration of 0.5% (v/v). Castor oil concentration of 3.0% (v/v) showed 34.21 and 63.20% mortality for indirect and direct application, respectively. Mortality caused by indirect and direct application on the coffee berry borer increases with increasing concentration of castor oil. The way of applying direct from castor oil on the coffee berry borer showed LC50 of 2.05% (v/v).